Upaya Perbaikan Kualitas Menggunakan Metode Six Sigma untuk Mengurangi Jumlah Cacat Produk Head Travel Kit pada PT. Berlina Tbk - Diajeng Rizky Amelia; Rina Sandora; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
In packaging industries, PT. Berlina is enganged in the production of plastic packaging, especially in injection moulding departement based on September 2019 data, there is a product that has the largest percentage of defects namely head travel kit (9.1%). Bubble defect is the most dominant problem among other disability categories with a percentage of 57.9%. This study aims to know and identify the factors that cause bubble defect and determine alternative improvement policies that can reduce the rate of occurance of bubble defects of head travel kit product to implement. The method use in this study is Six Sigma which includes five stages of analysis, namely DMAIC (Define, Measure, Analyze, Improve, and Control). Each stage of DMAIC is done by carefully analyzing and maintaining the process. The results of this study indicate that the factors causing bubble analyzed by FTA are speed injection parameters exorbitant, plastizing process less precise, back pressure parameter too low, and ventilation syste, less precise. There are plan of improvement effort that is varying the speed injection parameter, extend the holding time parameter, extend the back pressure parameter, and cleaning the venting area. While the effort improvement that has be done is verying the speed injection parameter with a range of 15 mm/s untul 25 mm/s and extend the holding time parameter to 6 secon.The result of effort improvement are showed the decrease of defects percentage between before and after improvement that is from 26 % to 10 % and obtained 3,145 sigma, it means more and better than from previous sigma value, it is 2,849 sigma.